Reconsidering the scribbling stage of drawing: a new perspective on toddlers' representational processes - Quaglia, Rocco; Longobardi, Claudio; Iotti, Nathalie O. (Frontiers in Psychology, 2015)
Although the scribbling stage of drawing has been historically regarded as meaningless and transitional, a sort of prelude to the "actual" drawing phase of childhood, recent studies have begun to re-evaluate this important moment of a child's development and find meaning in what was once considered mere motor activity and nothing more. The present study analyzes scribbling in all its subphases and discovers a clear intention behind young children's gestures. From expressing the dynamic qualities of an object and the child's relationship with it, to gradually reducing itself to a simple contour of a content no more "alive" on the paper, but only in the child's own imagination, we trace the evolution of the line as a tool that toddlers use to communicate feelings and intentions to the world that surrounds them. We will provide a selected number of graphical examples that are representative of our theory. These drawings (13 in total) were extracted from a much wider sample derived from our studies on children's graphical-pictorial abilities, conducted on children aged 0 to 3 years in various Italian nurseries. Our results appear to indicate that scribbling evolves through a series of stages, and that early graphical activity in children is sparked and maintained by their relationship with their caregivers and the desire to communicate with them.